Does negative pressure wound therapy with saline instillation improve wound healing compared to conventional negative pressure wound therapy? - A randomized controlled trial in patients with extremity ulcers. (January 2021) - Giri, Prakriti; Krishnaraj, Balamourougan; Chandra Sistla, Sarath; Sistla, Sujatha; Basu, Debdatta; Shankar, Gomathi; Akkilagunta, Sujiv; Ruparelia, Jigish
Abstract: Background: Wounds are important health problems that cause significant financial burden and loss of time to work, more so in low and lower middle income countries. Negative pressure wound therapy (NPWT) is widely established in managing acute and chronic extremity wounds. We studied the effects of addition of normal saline instillation to NPWT in terms of changes in granulation tissue, bacterial-burden and overall wound healing using readily available means and materials including wall suction for negative pressure, sponge and adhesive transparent sheet for dressing and normal saline for irrigation. Methods: All patients with extremity ulcers initially underwent surgical debridement. They were then allotted into two groups, group 1 (NPWT with normal saline instillation- NPWTi) including 25 patients and group 2 (NPWT) including 23 patients. Tissue-bit samples taken on day1 and day 10 were used for bacteriology and for assessing histology. The wound surface-area was measured using the software ImageJ on day 1 and day 10. Results: Median log difference in colony-count between day1 and day10 was 0.6 (0.2–1.4) in group1 and 0.13 (0.04–0.6) in group 2 (p < 0.05). Mean percentage reduction in wound size was 28.82 and 19.80 in group 1 and group 2 respectively (p < 0.05). Histological parameters of wound healing assessed as surface epithelium, granulation, inflammatory cells, proliferative blood-vessels and fibroblasts were significantly better in group1. A drawback observed with NPWTi was skin maceration around the ulcer which was successfully managed. Conclusion: Our findings suggest that wound healing is significantly better when saline instillation is combined with NPWT. It can aid in complex extremity ulcers management by reducing the size of the wound with healthier looking granulation tissue. Highlights: Wound healing requires adequate infection control, improved microcirculation and healthy granulation as seen with NPWT. NPWT with saline instillation (NPWTi) has gained popularity in past few years for management of extremity ulcers. NPWTi reduces bacterial bioburden, promotes granulation tissue and reduces wound size which leads to better wound healing. This is the first prospective randomized controlled trial comparing conventional NPWT to NPWTi using saline irrigation.